Acculturation and wellbeing - Tseu, Anne (2020)
This mixed methods study investigated the acculturation status and wellbeing of a sample of first-generation immigrants to Canada. The participants were among students taking an Introductory Psychology course at a Canadian university. Interviews were conducted to collect demographic data on the participants, as well as their views on their experience of their country of origin and their current experience in Canada. In addition, their retrospective ratings of their subjective wellbeing before they left their country of origin, as well as their current ratings of their wellbeing in Canada were collected using the Personal Wellbeing Index (PWI) (International Wellbeing Group, 2005). T-test comparisons between the retrospective ratings of the participants prior to immigrating and their current ratings in Canada on the PWI indicated significantly higher levels of satisfaction in the domains of standard of living, achievement in life , personal safety and future security since moving to Canada. The qualitative interview data was reviewed to determine the acculturation status of the participants. The comparison of the PWI ratings between participants in the integrated and assimilated categories found that those categorized as integrated rated themselves more satisfied across all of the life domains as well as on life as a whole although the difference was significant only for the personal relationships domain. While this study was based on a very small sample it does point the way to a further research with possible policy implications.